DOI: 10.7190/shu-thesis-00223
|View full text |Cite
|
Sign up to set email alerts
|

Bone Vibration Analysis as a Novel Screening Tool for Long Bone Fractures

Abstract: The aim of this study is to reduce the number of X-ray scans taken to detect fractures, by developing a bone fracture screening system. When assessing a bone injury, doctors need to decide whether the injury has resulted in a fracture or a sprain so that they can provide appropriate treatments. The current way to differentiate between these is by an X-ray scan. In 2011, the 46,000 children attending Sheffield Children's Hospital Emergency Department had 10,400 X-rays, mostly to help diagnose bone fractures. Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Some related studies have found that the response varies depending on the presence or absence of fracture. 2,3,5–9 In particular, there are different responses at low and high frequencies, and this has also been observed in experiments. The present study develops an intelligent system to detect these characteristic responses and features.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Some related studies have found that the response varies depending on the presence or absence of fracture. 2,3,5–9 In particular, there are different responses at low and high frequencies, and this has also been observed in experiments. The present study develops an intelligent system to detect these characteristic responses and features.…”
Section: Introductionmentioning
confidence: 54%
“…Various medical techniques, such as X-rays, computed tomography (CT), and fork tuning systems, have been developed and are widely used. In addition, more advanced technologies are currently emerging in the field of medical engineering 14 Radiography-based approaches, such as CT, X-Ray, electromagnetic interference (EMI), and positron emission tomography (PET)/CT are capable of accurately monitoring various pathological and trauma-induced conditions with some side effects. For the rapid detection of bone fractures without the need for radiation exposure, this research proposes the measurement and analysis of the transverse vibration responses of bones considering the bilateral symmetry of the human body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation